The perspective of women, youth and older adults in the face of the new rurality - Gómez Rojo, Rosa Estela; Castellanos Suárez, José Alfredo (Revista Mexicana de Ciencias Agrícolas, 2018)
What is a new rurality attributed to? There is much debate about the new rurality, on the one hand it is attributed as a current study for agrarian issues, stimulating new research in rural transformations or simply a new concept that gained popularity to what already existed. The term became more common and was used improperly for political purposes and to promote the legitimacy of certain actions. The concept of new rurality is analyzed and the impact it has had through three social actors, which were not mentioned in studies of yesteryear on issues of the field: women, young people and older adults, seen as new actors or simply were invisible in the tasks of the field.
Keywords: adolescents and older adults, new rurality, rural-urban relationship, women